An infection-induced RhoB-Beclin 1-Hsp90 complex enhances clearance of uropathogenic Escherichia coli - Chunhui Miao (Nature Portfolio, 2021)
Bacterial invasion can lead to multiple host cell responses. Here, the authors show that in a model of uropathogenic E. coli, RhoB is upregulated and induces autophagosome formation in a complex with Beclin1 and Hsp90, promoting bacterial clearance.